Improving Methods Work Productivity of Medical Record Room Staff in Hospital Management Information a Regional General Hospital of Padang Sidempuan - Nadia Zenni Andari; Sri Lestari Ramadhani Nasution; Ali Napiah Nasution; Ermi Girsang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine and describe the work productivity of staff in the medical record room in the implementation of HMIS in Padangsidimpuan City Hospital and what factors influence it. This research is a kind of survey research with a descriptive non hypothesis qualitative approach. The population in this study was the staff in the medical record room at Padangsidimpuan City Hospital with a sample size of 20 staff (total population units). Research data were collected through interviews and questionnaires. The data analysis technique used is descriptive analysis with percentages. The findings of the study showed that the majority of staff in the medical record room had a high work productivity category in the implementation of HMIS activities in Padangsidimpuan City Hospital, as many as 60% while 40% of staff had low work productivity. The analysis shows that work motivation, ability, wages, work environment, and staff work discipline are factors that influence the work productivity of staff in the medical record room in the implementation of HMIS. Thus, it was concluded that the majority of staff in the medical records room at Padangsidimpuan City Hospital had high category productivity and factors affecting the work productivity of staff in the medical record room in the implementation of HMIS activities at the Padangsidimpuan City Hospital, including work motivation, staff ability, wages, work environment, and work discipline.